A reduced hardware complexity algorithm with improved outage probability for 5G communication system. (3rd January 2022) - Taneja, Ashu; Saluja, Nitin
In this paper, a 5G mobile communication system is considered with cooperative environment. The mobile and base-station node communicate with each other through a number of amplify-and-forward (AF) relays. The users have multiple antennas while each relay has a single antenna. The radio-frequency (RF) transceiver chain associated with each antenna element leads to increased hardware complexity. This challenge is reduced by efficient utilisation of RF front ends in the proposed wireless system. The paper proposes an RF chain selection technique which enables the selection of RF front end with maximum received signal-to-noise-ratio (SNR). The outage probability is derived for proposed mobile communication system. Further, system ergodic capacity, energy efficiency and average end-to-end SNR are evaluated. As compared to the conventional random selection approach, this algorithm aims to achieve higher capacity and higher average end-to-end-SNR. At 16 dB SNR, system capacity improves by 52% with proposed algorithm rather than conventional random selection.